2004
DOI: 10.1111/j.1440-1738.2004.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Zircon U–Pb ages and tectonic implications of ‘Early Paleozoic’ granitoids at Yanbian, Jilin Province, northeast China

Abstract: The Yanbian area is located in the eastern part of the Central Asian Orogenic Belt (CAOB) of China and is characterized by widespread Phanerozoic granitic intrusions. It was previously thought that the Yanbian granitoids were mainly emplaced in the Early Paleozoic (so-called 'Caledonian' granitoids), extending east-west along the northern margin of the North China craton. However, few of them have been precisely dated; therefore, five typical 'Caledonian' granitic intrusions (the Huangniling, Dakai, Mengshan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 25 publications
4
128
0
Order By: Relevance
“…7, Wu et al, 2000). (3) In the Yanbian area, the reported oldest granitoid was formed at 285 Ma (Zhang et al, 2004), which has similar Sr-Nd ( 87 Sr/ 86 Sr(i) = 0.706, ε Nd (t) = −13.6) isotopic compositions to the Mashan Group. (4) Cao et al (2013) reported that a middle Permian garnet-bearing monzogranite from central Jilin province (about 200 km northwest to the Yanbian area) had zircon ε Hf (t) values from −17.1 to −14.1, and with Hf single-stage model ages (T DM1 ) of 1.51-1.66 Ga. All these facts reflect the existence of recycled crustal rocks at lower-middle crustal levels in the Yanbian and adjacent areas.…”
Section: Crustal Contamination or Afc Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…7, Wu et al, 2000). (3) In the Yanbian area, the reported oldest granitoid was formed at 285 Ma (Zhang et al, 2004), which has similar Sr-Nd ( 87 Sr/ 86 Sr(i) = 0.706, ε Nd (t) = −13.6) isotopic compositions to the Mashan Group. (4) Cao et al (2013) reported that a middle Permian garnet-bearing monzogranite from central Jilin province (about 200 km northwest to the Yanbian area) had zircon ε Hf (t) values from −17.1 to −14.1, and with Hf single-stage model ages (T DM1 ) of 1.51-1.66 Ga. All these facts reflect the existence of recycled crustal rocks at lower-middle crustal levels in the Yanbian and adjacent areas.…”
Section: Crustal Contamination or Afc Processesmentioning
confidence: 99%
“…The mafic intrusions were previously considered to have formed in late Paleozoic, but the precise emplacement ages are lacking. The Mesozoic geological evolution of the area was characterized by eruption of voluminous lavas, granitoid emplacement and deposition of terrestrial sediments, probably as a result of subduction of the paleo-Pacific Ocean (Zhang et al, 2004;Li et al, 2007;Xu et al, 2013b;Guo et al, 2015).…”
Section: Geological Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations
“…13b , , 1965Kon and Takagi, 2012;, 2015, 1990Ishiwatari and Tsujimori, 2003 Fig . 13b Zhou --, 1992, 2010;-, 1965Kawamura et al, 2007, 1992Nishimura, 1998300 Ma , 2001, 2008Tsutsumi et al, 2010;, 2013;Watanabe et al, 1995-, 2001, , 2002Ishiwatari and Tsujimori, 2003Zhou et al, 2010, Ishihara et al, 1996Zhang et al, 2004 230 Ma , Isozaki et al, 2014Isozaki et al, , 1990Ehiro, 2001;Okawa et al, 2013Okawa et al, , 2000Okawa et al, , 2004, 201420101990 2011 …”
mentioning
confidence: 99%